2002
DOI: 10.1016/s0886-3350(01)01269-x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic intracameral cefuroxime

Abstract: Intracameral cefuroxime 1 mg appeared to effectively inhibit sensitive bacterial strains and was associated with a low frequency of postoperative endophthalmitis. The causative organisms of future incidents of postoperative endophthalmitis will determine whether the present protocol must be reappraised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(48 citation statements)
references
References 16 publications
1
40
2
5
Order By: Relevance
“…From the review of bibliographical references of the primary studies included and a manual search, three additional references were located. Therefore, seven references were finally included in this phase: one clinical trial reported in two papers,6,14 four observational studies,8,15–17 and an economic evaluation 18…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the review of bibliographical references of the primary studies included and a manual search, three additional references were located. Therefore, seven references were finally included in this phase: one clinical trial reported in two papers,6,14 four observational studies,8,15–17 and an economic evaluation 18…”
Section: Resultsmentioning
confidence: 99%
“…The onset of endophthalmitis was 0.42% in the control group (period up to 2004), compared with 0.13% in the group that received cefuroxime (period between 2004 and 2007) ( P =0.031) (Table 1). A study performed in Sweden in 20028 with a similar design included two cohorts. The first one included 34,102 participants operated on for cataract between 1990 and 1995 without intracameral prophylaxis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the studies regarding prophylaxis of endophthalmitis, Montan et al[ 9] reported that intracameral cefuroxime-axetil appeared to effectively inhibit sensitive bacterial strains and was associated with a low frequency of postoperative endophthalmitis. However, we had a high Gram-negative organism isolation rate (33.3%) with a low susceptibility rate for cefuroxime-axetil (12%).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of topical antibiotics in preventing bacterial postoperative endophthalmitis (POE) has been controversial [17,18,19], the prophylactic use of antibiotics before, during and/or after the operation is common. It was suggested that this treatment helps prevent bacterial POE by sterilizing the ocular surface and by penetrating the ocular tissues to provide intracameral antibiotic concentrations to eliminate bacteria that may enter the eye during surgical intervention.…”
Section: Discussionmentioning
confidence: 99%